Public Housing of Early Modern Tianjin (1928-1937) - Sun, Yanchen; Hein, Carola; Song, Kun; Wang, Jianghua (International Planning History Society Proceedings, 2016)
Societal reform, the planning and construction of public housing and the introduction of new building typologies went hand in hand in early modern China. Western and Japanese debates on public housing served as models, and Chinese scholars and professionals with the support of the KMT (Kuomintang) developed public housing as a sign of innovation both in terms of societal organization and building typology. Using the under-researched case of Tianjin’s public housing in the so-called Golden Decade (1928 -1937) as a case study, the paper first explores how journals and foreign trained Chinese scholars introduced the concept of modern housing to China through publications, and early constructions. Notably the YMCA Labours Model New Village in Shanghai impressed the KMT leader Chiang Kai-shek. It then explores three public housing projects developed for Tianjin, only one of which was realized. Exploring the locations, architectural designs, renting regulations and management rules of these projects, the paper argues that these projects (both planned and realized) aimed mostly at poor families, and served as a means to solve housing problems and reform society as well as to police the poor. The public housing projects in this period formed the foundation for later public housing in China.